The Rights and Responsibility of Test Takers when Large-Scale Testing Is Used for Classroom Assessment - van Barneveld, Christina; Brinson, Karieann (Canadian Journal of Education/Revue canadienne de l’éducation, 2017)
The purpose of this research was to identify conflicts in the rights and responsibility of Grade 9 test takers when some parts of a large-scale test are marked by teachers and used in the calculation of students’ class marks. Data from teachers’ questionnaires and students’ questionnaires from a 2009–10 administration of a large-scale test of Grade 9 mathematics were analyzed using descriptive statistics. Written comments by teachers were analyzed into themes. Results were interpreted using a framework comprised of a policy document and two theories that are relevant to large-scale testing: the rights and responsibility of test takers as documented in the Standards for Educational and Psychological Testing (AERA/APA/NCME/JCSEPT, 2014), expectancy-value theory of motivation, and theory regarding the developmental stage of students in Grade 9. Several conflicts were identified. Potential solutions to conflicts were presented.